POTRET PEDAGANG KELILING DALAM KARYA SENI LUKIS REALIS KONTEMPORER - WAHYU KURNIAWAN, Drs. Abd. Hafiz, M.Pd, Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2015)
This thesis aims to give the view that the importance of a proper jobwould improve the level of a person's life, as well as provide apresiasai against peddlers who work hardest of all the limitations. At the end of the work of this author portrait peddlers who represent the theme and concept. Subject mater shown lifting portrait pitchman together luggage. This thesis focuses penggarapannya with contemporary realist style and enhances dimensional shape of the object in it. Based on all the limitations, the types of mobile vendors, as well as the uniqueness and struggles that are then visualized in contemporary realist paintings, as well as being a learning and muse for writers, society and government.Kata kunci: Pedagang keliling, Realis kontemporer